Aboriginal and non-Aboriginal children in Western Australia carry different serotypes of pneumococci with different antimicrobial susceptibility profiles. Issue 1 (December 2016) - Dunne, Eileen; Carville, Kylie; Riley, Thomas; Bowman, Jacinta; Leach, Amanda; Cripps, Allan; Murphy, Denise; Jacoby, Peter; Lehmann, Deborah
Abstract Background Carriage ofStreptococcus pneumoniae is considered a precursor to pneumococcal diseases including pneumonia. As part of the Kalgoorlie Otitis Media Research Project, we characterised pneumococci isolated from the nasopharynx of Western Australian Aboriginal and non-Aboriginal children. Methods Between 1999 and 2005, 100 Aboriginal and 180 non-Aboriginal children were followed from birth to two years, with nasopharyngeal aspirates collected at ages 1–3 and 6–8 weeks, then at 4, 6, 12, 18 and 24 months. Introduction of 7-valent pneumococcal conjugate vaccine (7vPCV) in 2001 enabled evaluation of its impact on carriage in study participants according to vaccines doses received. Pneumococcal serotyping was performed by Quellung and antimicrobial susceptibility by disk diffusion and Etest®. Molecular epidemiology of pneumococcal isolates was investigated by pulse-field gel electrophoresis and multilocus sequence typing. Results Overall, the prevalence of 7vPCV serotypes was similar for Aboriginal and non-Aboriginal children (19 % vs. 16 %), but the prevalence of non-vaccine serotypes was higher in Aboriginal children (22 % vs. 7 %). A multi-resistant 6B clone (ST90) was found only in non-Aboriginal children. Aboriginal children who received three doses of 7vPCV had lower odds of carrying 7vPCV serotypes (odds ratio [OR] 0.19, 95 % CI 0.08–0.44) and higher odds of carrying non-vaccine serotypes (OR 2.37, 95 % CI 1.13–4.99) than unvaccinated Aboriginal children; this finding was not observed in non-Aboriginal children. Conclusions This unique study shows important differences in pneumococcal serotypes, genotypes, and antimicrobial susceptibility between Aboriginal and non-Aboriginal children living in the same geographic area before widespread 7vPCV use, and highlights the need for ongoing post-vaccination surveillance in outback Australia.